HARMONISASI DIRECT LICENSING DAN COLLECTIVE LICENSING ATAS PERFORMING RIGHTS DI INDONESIA - Baity, Sheila Noor; Rakhmawati, Catur Septiana (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to address two legal issues: First, the weaknesses in the Copyright Law and its implementing regulations regarding the application of direct licensing—particularly for performing rights—with a focus on the subjects, licensing system, and the role of Collective Management Organizations (LMK) and the National Collective Management Organization (LMKN). Second, efforts to harmonize the regulation of direct and collective licensing in Indonesia by comparing the legal frameworks for direct licensing in the United States and Australia. This is a normative legal study that relies on secondary data and employs qualitative analysis. The findings reveal that the regulatory weaknesses in Indonesia concerning direct licensing include the unclear identification of royalty recipients, the absence of a recognized licensing system, and the provisions governing LMKN and LMK under the Government Regulation on Royalties (PP Royalti), which effectively nullify the right to direct licensing as stipulated in the Copyright Law. This study proposes several recommendations for harmonizing the regulation of direct and collective licensing in Indonesia: First, clarifying the legal subjects entitled to royalties in the Copyright Law by clearly defining the terms “any person” and “user.” Second, harmonizing relevant regulations, particularly Government Regulation No. 56 of 2021. Third, improving the role of LMKN either as a regulator and mediator or by delegating its implementation to the Directorate General of Intellectual Property (DJKI).